Pengaruh Peran Kepala Sekolah Terhadap Kinerja Guru SMK Kecamatan Tompaso Baru - Febryani Maureen Lidya Rattu (Indo Publishing, 2026)
The background to this research is the reality that shows the low performance of Tompaso Baru Vocational School teachers. The role of the school principal is a factor that influences low teacher performance. This research uses a quantitative research approach and an ex post facto type of research. The research population was all 75 teachers at Tompaso Baru Vocational School District. The number of research samples is the same as the population. The analysis of this research includes normality test analysis, homogeneity test, linearity test, and multicollinearity test. Hypothesis tests include correlation tests, Anova tests, summary tests, and regression coefficient tests. The research results show that there is a positive influence of the role of the principal on teacher performance by 34.6%. Coaching is needed to improve the role of school principals so that teacher performance also increases.